Structure of News Text on the Arrest of the Head of Front Pembela Islam in Online Media - Lina Putriyanti (Buletin Al-Turas, 2022)
PurposeThe study was to find and describe the structure of the news text on the arrest of the Front Pembela Islam chairman in cases of violating health protocols in the midst of the Covid-19 pandemic on BBC News Indonesia and Kompas.com online mediaMethodThe research was a descriptive qualitative by utilizing van Dijk's model with a social cognition approach focusing on the text schemes which included macro structure, superstructure, and micro structure. The research data were the fragments of discourse of articles on online media BBC News Indonesia and Kompas.com which contained news of healt protocals violations. The research applied listening technique and a note-taking technique as a follow-up. To check the research data, triangulation and interactive analysis techniques were needed to analyze the data.Results/FindingsThis study foud out that the online media BBC News Indonesia and Kompas.com had a macro structure regarding the arrest of Rizieq Shihab for violating one of the Covid 19 health protocols, that was gathering crowds. the superstructure was found in the introduction, content, and closing; the microstructure section was found in semantics (background and intent), syntax (sentence forms and pronouns), lexicon, and graphics.ConclusionThe study concluded that according to the Teun A van Dijk scheme, the news on Rizieq Shihab's health protocol violations during the Covid 19 pandemic of BBC News Indonesia and Kompas.com had a macro text structure, superstructure, and micro structure.